Kenaikan Suku Bunga Acuan Dan Perlambatan Konsumsi Rumah Tangga Di Indonesia - Khairunnisa Muthmainnah; Muhammad Arif Farhan; Najwa Minhatul Mawla; Syafaatul Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effect of benchmark interest rate increases on the slowdown of household consumption in Indonesia from a macroeconomic perspective. Household consumption is the largest contributor to Indonesia’s Gross Domestic Product and plays an important role in maintaining national economic stability. In recent years, Bank Indonesia has implemented a tightening monetary policy through increases in benchmark interest rates in response to global inflation pressures, exchange rate instability, and uncertainty in the international financial market. This study employs a qualitative approach using a literature review method by analyzing scientific journals, government reports, and macroeconomic publications issued within the last five years. The research process was carried out through the identification of benchmark interest rate developments, analysis of the relationship between interest rates and household consumption, and interpretation of the impact of monetary policy on Indonesia’s macroeconomic stability. The findings indicate that increases in benchmark interest rates significantly affect household purchasing power, consumption credit growth, and public spending patterns. Higher interest rates encourage households to reduce non-essential spending and increase savings due to higher borrowing costs and economic uncertainty. In addition, the slowdown in household consumption has implications for aggregate demand, investment growth, and national economic performance. The study concludes that although increasing benchmark interest rates is necessary to maintain inflation and exchange rate stability, balanced coordination between monetary and fiscal policy is essential to sustain household purchasing power and long-term economic growth in Indonesia.